Industrial Efficiency, Social Order and Moral Purity: Housing Reform Thought in English Canada, 1900–1950 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1997)
This paper traces the evolution of reform ideology in the housing sphere in the first half of the twentieth century by critically analyzing the ideas and practices of a number of key housing reformers and agencies. Premised on middle-class beliefs in the necessity of state intervention and the capacity of the trained expert to alleviate social conflict, the movement for housing betterment centred on a doctrine of “community” that ostensibly stood above labour and capital, aiming to harmonize social relations for the greater good of the nation. To this end, stress was placed on bettering the physical conditions of workers' dwellings in order to improve the productive capacity of the labour force. But the concentration on the physical quality of workers' homes was also tied to the wider ideological goal of strengthening the nuclear family — a cornerstone of the nation and the state in the estimation of reform-minded citizens. The role housing reform could play as part of the larger project of securing social consent by stabilizing family structures and contributing to the construction of a distinct national identity constituted pivotal concerns in the discourse of the reform effort. Progressives aimed to extend state intervention in the housing sphere in order to allay the impact of industrialization and preserve class cooperation and social hierarchy. Yet without losing sight of this distinct regulatory thrust from above, it is also necessary to chart how housing experts and policy makers groped through the contradictions of urban society in a creative manner they themselves saw as more or less disinterested.